2016
DOI: 10.1002/hep.28477
|View full text |Cite
|
Sign up to set email alerts
|

A low‐cost, user‐friendly electroencephalographic recording system for the assessment of hepatic encephalopathy

Abstract: Electroencephalography (EEG) is useful to objectively diagnose/grade hepatic encephalopathy (HE) across its spectrum of severity. However, it requires expensive equipment, and hepatogastroenterologists are generally unfamiliar with its acquisition/interpretation. Recent technological advances have led to the development of low-cost, user-friendly EEG systems, allowing EEG acquisition also in settings with limited neurophysiological experience. The aim of this study was to assess the relationship between EEG pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…The application of simpler EEG systems (6-channels, for example) is also being explored for emergency settings (Jakab et al, 2014 ). A prior evaluation, although utilizing a more complex headset, showed that commercially available multi-lead consumer EEG systems, such as the Emotiv EPOC 16-electrode cap, may also have value in evaluating clinical conditions (Schiff et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of simpler EEG systems (6-channels, for example) is also being explored for emergency settings (Jakab et al, 2014 ). A prior evaluation, although utilizing a more complex headset, showed that commercially available multi-lead consumer EEG systems, such as the Emotiv EPOC 16-electrode cap, may also have value in evaluating clinical conditions (Schiff et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of EEG in daily clinical work is becoming more and more feasible with new devices emerging, offering drastically reduced mounting times while retaining the quality of recordings (Schiff et al, 2016). This shows EEG to be a potential important part in personalized pain medicine, with the potential to reduce suffering and persistent postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…This shows EEG to be a potential important part in personalized pain medicine, with the potential to reduce suffering and persistent postoperative pain. The use of EEG in daily clinical work is becoming more and more feasible with new devices emerging, offering drastically reduced mounting times while retaining the quality of recordings (Schiff et al, 2016). Future studies should work towards optimization of the methods together with inclusion of more variables in combination with the EEG.…”
Section: Discussionmentioning
confidence: 99%
“…Computerised psychometric tests (Continuous Reaction Time [75,76], Inhibitory Control Task [77], Scan test [34,68] and the Stroop test [78]), and EEG [79] are also considered adequate in this respect according to the EASL/AASLD joint guidelines of 2014 but are less commonly utilised [19]. Over recent years, efforts have been performed to make both neuropsychology (Stroop App [80]) and neurophysiology (cheap, light EEG recording systems [81]) tests available, transportable and quickly obtainable, also in settings with limited psychometric and neurophysiological experience such as liver wards and clinics. This, as long as obtained within defined operative boundaries and with a minimum of training and interdisciplinary cooperation, will hopefully result in a more widespread use of the tools.…”
Section: No Hepatic Encephalopathy Versus No Neuropsychiatric Impairmentmentioning
confidence: 99%